The Ultrastructure of Bone and Its Relevance to Mechanical Properties - Schwarcz, Henry P.; Abueidda, Diab; Jasiuk, Iwona (Frontiers in Physics, 2017)
Bone is a biologically generated composite material comprised of two major structural components: crystals of apatite and collagen fibrils. Computational analysis of the mechanical properties of bone must make assumptions about the geometric and topological relationships between these components. Recent transmission electron microscope (TEM) studies of samples of bone prepared using ion milling methods have revealed important previously unrecognized features in the ultrastructure of bone. These studies show that most of the mineral in bone lies outside the fibrils and is organized into elongated plates 5 nanometers (nm) thick, 80 nm wide and hundreds of nm long. These so-called mineral lamellae (MLs) are mosaics of single 5 nm-thick, 20 – 50 nm wide crystals bonded at their edges. MLs occur either stacked around the 50 nm-diameter collagen fibrils, or in parallel stacks of 5 or more MLs situated between fibrils. About 20% of mineral is in gap zones within the fibrils. MLs are apparently glued together into mechanically coherent stacks which break across the stack rather than delaminating. ML stacks should behave as cohesive units during bone deformation. Finite element computations of mechanical properties of bone show that the model including such features generates greater stiffness and strength than are obtained using conventional models in which most of the mineral, in the form of isolated crystals, is situated inside collagen fibrils.